Case report: Ruptured aortic sinus aneurysm with left coronary artery aneurysm-right atrial fistula - Xiong, Wei; Long, Wei; Tang, Li; Liu, Jin; Song, Haibo (Frontiers in Anesthesiology, 2022)
A 50-year-old female presented with a history of fatigue after activities. Transthoracic echocardiography showed a 2.8 cm dilatation at the ostium of the left coronary artery and a 7.1×7.4 cm cyst-like aneurysm at the upper back of the left atrium, interlinking an anomalous fistula from the left coronary artery to the right atrial appendage, accompanied by moderate mitral and tricuspid regurgitation. Cardiac 3D-computed tomography identified the diagnosis of ruptured aortic sinus aneurysm (RASA) and a giant left coronary artery aneurysm fistula to the right atrium. Transesophageal echocardiogram and surgical vision confirmed these findings. Surgeries including RASA repair, coronary artery bypass grafting, and mitral and tricuspid valvuloplasty were then performed. Procedures proceeded successfully, the patient was fully recovered and discharged home.